Análisis de cuentas por cobrar de la Empresa Incubandina S.A. del cantón Montalvo - Llumiguano Guambuguete, Elizabeth Stefania (2020)
This case study is called Accounts Receivable Analysis of the company Incubandina S.A del Canton Montalvo which is a company dedicated to the incubation, reproduction, raising and distribution of poultry etc. It tends to be a company that is uncertain in the poultry effort, it is dedicated to the Production of BB Chicks for laying and meat lines, its farms and plants are located in the City of Montalvo. As we know, every entity needs to grant credits when making its sales since it is considered a primary strategy to maintain and attract customers and therefore have economic growth, but the problem arises when the agreed term time for the debt granted to be canceled ends and customers have not been able to pay and that is when the existence of an overdue portfolio arises The objective of this study is to know how this situation affects the liquidity of the company through an analysis of the effects of having an overdue portfolio, through the application of Financial Ratios that help to better interpret the economic situation of the same.